Sports Nutrition - Current Recommendations - Schek A; Braun H; Carlsohn A; Großhauser M; König D; Lampen A; Mosler S; Nieß A; Oberritter H; Schäbethal K; Stehle P; Virmani K; et al. (Dynamic Media Sales Verlag, 2020)
This position statement represents the current state of scientific knowledge regarding the recommended fat intake in ambitious recreational and high level sports. It also addresses dietary strategies (fat-loading methods) and food supplements that are designed to influence fat metabolism during physical exercise.No recommendation has so far been established for sports-specific fat intake in absolute numbers (g/kg body weight [BW]/d), in line with international practices regarding carbohydrate and protein. However, there is consensus among scientific sports medicine associations that fat consumption should not exceed 30% of the energy intake (E%), nor fall below 20 E%, particularly in endurance sports.Before competitions, some athletes practice fat-loading strategies which include a ketogenic diet. This procedure is not advisable, as there is no scientific evidence of improvement in either endurance (>70% VO2max) or sprint/strength performance. Moreover, the extensive restriction of carbohydrate intake is not in accordance with the internationally-accepted nutritional guidelines for athletes, and the food choice is unbalanced according to the recommendations of the German Nutrition Society (DGE).The current use of dietary supplements which are supposed to improve the availability/oxidation of fatty acids, e.g. caffeine, carnitine, fish oil, middle chain triglycerides (MCT), is also generally discouraged. Key Words: Dietary Supplements, Ketogenic Diet, Carnitine, Fish Oil, Middle Chain Triglycerides (MCT)